Magnetorheological finishing on metal surface: a review - N. A., Mutalib; I., Ismail; S. M., Soffie; S. N., Aqida (IOP Publishing, 2019)
Magnetorheological finishing (MRF) process is capable to fabricate an ultra-fine surface from flat to three-dimensional profile structures using Magnetorheological polishing fluid MRPF). MRPF is a smart fluid that can change from liquid to near solid state under the influences of magnetic field. Abrasive particle is essential material in MRPF. Three main methods in MRF process are reviewed including composition of the MRPF, rheological properties and polished surface quality.